2012
DOI: 10.1007/s10103-012-1099-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental periodontitis in rats using repeated adjunctive antimicrobial photodynamic therapy

Abstract: The aim of this study was to histologically and histometrically evaluate the influence of repeated adjunctive antimicrobial photodynamic therapy (aPDT) on bone loss (BL) in furcation areas in rats. Periodontitis was induced by placing a ligature around the mandibular molar in 75 rats. The animals were divided into five groups: the SS group was treated with saline solution (SS); the SRP group received scaling and root planing (SRP); the aPDT1 group received SRP as well as toluidine blue (TBO) and low-level lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
4
25
0
2
Order By: Relevance
“…Significant differences were observed at 7 d (ASU/+7) and 15 d (ASU/0 and ASU/+7) but were not confirmed at 30 d. Despite the long‐term benefits reported following administration of ASU in animal models of arthritis induction and in clinical studies , it is possible that the absence of differences between the groups on day 30 may be caused by the experimental model of periodontitis induction used in our study. Indeed, the ligature was maintained in the subgingival sulcus for 7 d, and it was previously shown that removal of the ligature induces periodontal repair . This was confirmed in our study because all groups showed bone‐tissue repair with increasing observation periods.…”
Section: Discussionsupporting
confidence: 89%
“…Significant differences were observed at 7 d (ASU/+7) and 15 d (ASU/0 and ASU/+7) but were not confirmed at 30 d. Despite the long‐term benefits reported following administration of ASU in animal models of arthritis induction and in clinical studies , it is possible that the absence of differences between the groups on day 30 may be caused by the experimental model of periodontitis induction used in our study. Indeed, the ligature was maintained in the subgingival sulcus for 7 d, and it was previously shown that removal of the ligature induces periodontal repair . This was confirmed in our study because all groups showed bone‐tissue repair with increasing observation periods.…”
Section: Discussionsupporting
confidence: 89%
“…Pathological results showed that there were a lot of inflammatory cells infiltration, seldom fibroblasts of connective tissue disorganization, and bone loss in coronal furcation. These clinical and pathological alterations are in line with those of other experimental periodontitis model establishment reported by other investigators [20, 21]. …”
Section: Discussionsupporting
confidence: 92%
“…Regarding IL-10 immunolabeling, which is associated with inhibition of bone resorption [37], there was higher immunolabeling in group 5FU/SRP/aPDT compared with groups EP, 5FU, and 5FU/SRP. This finding might be justified by the highest reduction of periodontopathogens in animals treated with aPDT [38], which would reduce the release of pro-inflammatory cytokines, regulating bone metabolism and minimizing the immuno-inflammatory response. Although both evaluated therapies seem effective in the control of EP, further studies are needed to assess the effects of the protocols of these therapies for periodontal treatment in patients under chemotherapy.…”
Section: Discussionmentioning
confidence: 99%